ANALISIS STRUKTURAL-SEMIOTIK PANTUN DALAM PROSESI AKAD NIKAH MASYARAKAT MELAYU PONTIANAK - Pitaloka, Dian; Sulissusiawan, Ahadi; Muzammil, Ahmad Rabi'ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research describes the structure and meaning of pantun in the akad nikah procession of Pontianak Malay community. The method used is descriptive qualitative method. The data source is the pantun speaker or the pantun owner community. The data of this research is related to the analysis of pantun structure including diction, imagery, figurative language, and rhyme. The meaning of pantun is analyzed through heuristic and hermeneautic analysis. The techniques used are indirect techniques in the form of direct observation techniques and recording techniques, and direct techniques in the form of interviews. Data collection tools are in the form of interview sheets, image recording, and sound recording. Based on the analysis, the conclusion of this research is that there are pantun data that use four word choices per line, imagery using emotional imagery, figurative language using simile, and rhyming with a-b-a-b. The results of the heuristic and hermeneautic analysis have meanings such as conveying messages or advice in living their life.